A rare case of a gastric adenomyoma mimicking a gastric duplication cyst - Esra Elif Arslan,; Tuğba Acer Demir,; Lütfi Hakan Güney,; Merih Tepeoğlu,; Müge Sağnak Akıllı,; Akgün Hiçsönmez, (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Arslan EE, Acer Demir T, Güney LH, Tepeoğlu M, Sağnak Akıllı M, Hiçsönmez A. A rare case of a gastric adenomyoma mimicking a gastric duplication cyst. Turk J Gastroenterol 2018; 29: 613-5.